(untitled) (Eastern Medical College Journal, 2025)
Background: Association of Vitamin D receptor gene single nucleotide polymorphism and its association with various diseases have been previously researched, but its association with chronic obstructive pulmonary disease (COPD) has not been investigated yet. Objective: To evaluate the association between vitamin D receptor gene polymorphism (ApaI) and COPD. Methods: This study was conducted in the Department of Physiology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, from March 2019 to February 2020. For research, pulmonologists diagnosed 15 (fifteen) COPD patients with age 40 to 80 years (post-bronchodilator FEV1/FVC <0.70 and FEV1 <80% predicted) and 15 (fifteen) apparently healthy age-matched individuals (for comparison), were selected. The genetic assessment of (ApaI) was assessed by PCR-RFLPs. Data were stated as mean ± SD and percentage. The Independent sample‘t’ test and chi-square test were done for statistical analysis. In the interpretation of the results, ≤ 0.05 level of probability (p) was accepted as significant. Results: The frequency distribution of the ApaI VDR SNP was 20% (AA), 80% (Aa), 0% (aa) and 46.67% (AA), 40% (Aa), 13.33% (aa) COPD patients and healthy subjects, respectively. Furthermore, the AA (OR 0.28, 95% Cl 0.05-1.44, p = 0.12) and aa (p=0.14) were not associated with COPD. However, the heterozygous SNP of ApaI, Aa (OR 6, 95% CI 1.17-30.72, p = 0.02) was significantly associated with COPD. Conclusion: This study showed that ApaI of VDR SNP is associated with COPD. Eastern Med Coll J. July 2025; 10 (1): 33-39